Firm-Generated Content Vs User-Generated Content: Digital Content Strategies to Build Trust and Encourage Zakat Payments Through Formal Institutions - Muhammad Hanif Ibrahim; Imas Hasanah (The Asian Journal of Technology Management (AJTM), 2025)
Abstract. This study examines how firm-generated content (FGC) and user-generated content (UGC) can build trust and encourage zakat payments through formal institutions in Indonesia, where zakat potential is high but often channelled through informal means due to trust issues. Leveraging the Stimulus-Organism-Response (SOR) framework, the research explores how FGC and UGC influence perceived value and trust, ultimately shaping intentions to pay zakat through digital platforms. Data was collected from 269 respondents in Indonesia via an online survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). This study has a unique perspective by integrating SOR theory and digital content strategies to gain knowledge about community participation in zakat through formal institutions. Findings reveal that both FGC and UGC positively impact perceived value and trust, with perceived value and trust significantly influencing Zakat's payment intentions. However, zakat knowledge, while important, does not significantly moderate the effect of FGC and UGC on perceived value. These results suggest that high-quality, transparent content that resonates emotionally and authentically with muzaki is crucial in increasing engagement with formal zakat institutions. This study contributes to the literature on digital engagement strategies in non-profit sectors, providing practical insights for zakat institutions in leveraging FGC and UGC to enhance trust and encourage donations. By addressing both cognitive and emotional aspects of donor behavior, zakat institutions can strengthen public trust and increase zakat participation, supporting poverty alleviation efforts in Indonesia. Keywords: Digital Content Strategies, Firm-Generated Content, User-Generated Content, Zakat Institutions